Having Peers and Becoming One: Collective Consciousness among Civil Society Actors in China. Issue 106 (4th July 2017) - Wu, Fengshi
Abstract: Based on a unique survey of non-governmental organization (NGO) practitioners from diverse backgrounds, the article examines how these NGO practitioners view their peers and people alike, and the interconnectedness, unity and solidarity of the NGO sector. The research has found that mutual awareness and trust is strong at the interpersonal level among NGO practitioners, yet their views on the collective existence of an NGO and activism community remain divided. In addition, preliminary statistical analysis shows that particular work experiences such as connections with other NGOs and participation in policy advocacy are associated with the optimism of a shared community of social activism. More importantly, the more one has—or feels one has—having peers across organizations, the more favorably one thinks of the whole activism community. Therefore, the key to 'becoming a community' for civil society in China lies in 'having peers' for individual activists and NGO practitioners.